Bioequivalence of Two Oral Formulations of Triflusal Capsules in Healthy Volunteers - Quetglas, Emilio García; Campanero, Miguel Angel; Sádaba, Belén; Escolar, Manuel; Azanza, Jose Ramón (Arzneimittelforschung, 2008)
Triflusal (CAS 322-79-2) is an antiplatelet agent related to salicylates used in several European and Latin American countries in the treatment of cardiovascular diseases. The aim of this paper was to evaluate the bioequivalence of triflusal derived from two preparations using both parent drug and metabolite pharmacokinetic data.The bioavailability was measured in 24 healthy male Caucasian volunteers following a single oral dose (600 mg) of the test or reference products in the fasting state. Blood samples were collected for 120 h. Plasma concentrations of triflusal and its metabolite 3-hydroxy-4-trifluoromethylbenzoic acid (HTB) were analyzed by high-performance liquid chromatography with UV and fluorescence detection, respectively. The non-compart-mental method was used for pharmaco-kinetic analysis. Log-transformed Cmax, AUC0-t and AUC0-∞ were tested for bioequivalence using ANOVA and Schuirmann’s two-one sided t-test. Tmax was analyzed by nonparametric pharmacokinetic parameters of triflusal and HTB derived from the two formulations were nearly consistent with previous observations. Triflusal parameters derived from the test and reference drug were as follows: Cmax (16.85 ± 11.41 vs 14.48 ± 7.22 mg/l), AUC0-t (18.43 ± 10.91 vs 16.22 ± 7.58 mg/l per hour), Tmax (1 range 0.25–2h vs 0.875 range 0.25–1.5 h), and t1/2 (0.49 ± 00.27 vs 0.76 ± 0.64). HTB parameters after test and reference formulation administration were as follows: Cmax (68.13 ± 23.05 vs 65.51 ± 19.44 mg/l), AUC0-t (2748.18 ± 971.91 vs 2877.97 ± 881.2 h ∙ mg/l), AUC0-∞ (3350.15 ± 1182.62 vs 3372.49 ± 1110.35 h ∙ mg/l), Tmax (2 range 1–10 h vs 2 range 0.75-12 h), and t1/2 (42.19 ± 7.82 vs 43.13 ± 6.56 h). 90 % of confidence intervals for the test/reference ratio of Cmax, AUC0–t and AUC0–∞ derived from both triflusal and HTB were found within the range of 80 %–125 % acceptable for bioequivalence. No significant difference was found between the Tmax values for triflusal and HTB.It was concluded that the two preparations are bioequivalent and may be prescribed interchangeably.
Keywords: Anticoagulants; CAS 322-79-2; Triflusal, bioequivalence, capsule